REPORT ON THE HOLDING OF XI ALL-RUSSIAN SCIENTIFIC AND EDUCATIONAL FORUM "CARDIOLOGY 2009" (Столичная издательская компания, 2016)
Report on the holding of XI All-Russian scientific and educational forum "Cardiology 2009".